2021
DOI: 10.3390/agriculture11010069
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Branch Number and Yield Component of Soybean Cultivars Tested in Different Planting Densities

Abstract: Increasing planting density is one of the key management practices to enhance soybean yield. A 2-yr field experiment was conducted in 2018 and 2019 including six planting densities and two soybean cultivars to determine the effects of planting density on branch number and yield, and analyze the contribution of branches to yield. The yield of ZZXA12938 was 4389 kg ha−1, which was significantly higher than that of ZH13 (+22.4%). In combination with planting year and cultivar, the soybean yield increased signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Soybean yield in various countries, including China, has improved in recent years mainly because of genetic improvement, increased inputs (e.g., irrigation and fertilizer), and better field management practices, such as the optimization of planting density and tillage methods [5][6][7][8][9]. Increasing the planting density of soybeans can remarkably improve light interception and canopy photosynthesis, resulting in a significant increase in total dry matter accumulation and seed yield [9][10][11]. In the United States, a soybean record yield of 10,414 kg ha −1 was recorded in 2007, with a planting density of 520,000 plants ha −1 in Missouri by Kip Cullers [12].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Soybean yield in various countries, including China, has improved in recent years mainly because of genetic improvement, increased inputs (e.g., irrigation and fertilizer), and better field management practices, such as the optimization of planting density and tillage methods [5][6][7][8][9]. Increasing the planting density of soybeans can remarkably improve light interception and canopy photosynthesis, resulting in a significant increase in total dry matter accumulation and seed yield [9][10][11]. In the United States, a soybean record yield of 10,414 kg ha −1 was recorded in 2007, with a planting density of 520,000 plants ha −1 in Missouri by Kip Cullers [12].…”
Section: Introductionmentioning
confidence: 99%
“…According to their results, higher seed yield was positively correlated with higher plant populations. Xu et al [9] showed that the soybean yield could increase significantly by 16.2%, 31.4%, 41.4% and 46.7% for every increase in planting density of 45,000 plants ha −1 , within the range of 135,000 to 315,000 plants ha −1 . These studies collectively show that higher planting density improves seed yield.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations